THE INFLUENCE SURFACTANT AND THEIR MIXTURE WITH ELECTROLYTES ON GAS HYDRATE FORMATION (Oil and Gas Engineering, 2017)
The experimental results show that the temperature hydrateformation to presence of chemical components are reduced. There results represent practical value for development of new inhibitors hydrateformation and antyhydrate technologies in a gas industry. Keywords: hydrate, inhibitor, natural gas, hydrateformation, bischofite